Polarizing Magnetic Field Generator (Global Journal of Science Frontier Research, 2021)
Around the conductor with the current there is a magnetic field. If with the aid of the external current source was excited in the solenoid, or cylinder, thus it will be such to magnet with the appropriate poles. In the article is described the polarization generator of magnetic field, in which the magnetic field is created with the aid of the rotation of the polarized conducting cylinder.
Keywords: magnetic field; electric field; polarization; rotation